SPEECH ACTS OF MAIN CHARACTER IN AVATAR MOVIE SCRIPT - Roy Martin Sitanggang; Muhammad Natsir (State University of Medan, 2013)
Abstract This study is about the types of Speech acts used in Avatar movie script. The purpose of this study is to find out the types of speech acts base on George Yule’s theory and to find out which types are dominant in the script. The object of this study is a Avatar. This study analyzed the main character’s utterance. Jake Sully is the main character in Avatar movie. The study was conducted by using descriptive qualitative approach. They are five types of speech acts in Avatar movie script. They are declaratives acts are 3 items (0.85%), representatives acts are 176 items (50.28%), expressives acts are 48 items (13.71%), directives acts are 96 items (27.42%), and commissives acts are 27 items (7.71%). The data findings shown that representatives acts is dominantly used in this movie. There are 176 (50.28%) utterance that uttered by Jake Sully in Avatar movie script. Keywords: pragmatics, speech acts, avatar